Perbandingan Penyelesaian Tindak Pidana Pornografi Indonesia Dan Korea Selatan: Comparison Of The Resolution Of Pornography Crimes In Indonesia And South Korea - Raisha Arprilia; Gandes Candra Kirana (Faculty of Law, Universitas Trisakti, 2025)
The rapid advancement of technology has enabled society to access extensive knowledge but also brought negative impacts, such as the rise of pornography websites in Indonesia. Pornography encompasses images, videos, body movements, or messages containing obscene elements or sexual exploitation. This issue is prevalent not only in Indonesia but also in South Korea, where numerous pornography-related cases occur. This article examines the regulation and resolution of pornography crimes in Indonesia and South Korea, along with their respective strengths and weaknesses. Using a normative legal research method, this study analyzes primary and secondary data qualitatively with a deductive approach. The findings reveal differences in approaches: Indonesia emphasizes social and religious values, heavily influenced by its predominantly Muslim population. In contrast, South Korea, which is more diverse in terms of religion and culture, adopts a broader perspective, integrating social, cultural, and religious elements. South Korea has specific regulations and stringent law enforcement, particularly regarding digital technology. Meanwhile, Indonesia faces challenges in law enforcement due to societal and cultural factors. The resolution of pornography crimes in Indonesia and South Korea has its own strengths and weaknesses.